Agony and the Anthropos: Democracy and Boundaries in the Anthropocene. Issue 1 (1st March 2019) - Machin, Amanda
Abstract : The Anthropocene diagnosis, in which humanity has become a disruptive geological force, indicates an irresolvable political paradox. The political demos is inevitably and necessarily bounded. The Anthropocene, however, heralds the anthropos—the globalized more-than-human identity. The anthropos challenges the maintenance of political boundaries, yet any robust response to ecological predicament must be underpinned by a decisive demos. This article, informed by theories of political agonism, suggests that this paradox importantly provokes ongoing political contestation of the inevitable yet contingent exclusions from politics and the proper place of political boundaries in the Anthropocene. The article concludes that the Anthropocene diagnosis provides an opportunity for a lively democratic politics in which the demos is always prompted to reimagine itself and asks, who are "we" in the Anthropocene?